2022
DOI: 10.1073/pnas.2211534119
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability and clinical absorption of a form of encapsulated vitamin A for food fortification

Abstract: Food fortification is an effective strategy to address vitamin A (VitA) deficiency, which is the leading cause of childhood blindness and drastically increases mortality from severe infections. However, VitA food fortification remains challenging due to significant degradation during storage and cooking. We utilized an FDA-approved, thermostable, and pH-responsive basic methacrylate copolymer (BMC) to encapsulate and stabilize VitA in microparticles (MPs). Encapsulation of VitA in VitA-BMC MPs greatly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The results showed that encapsulated vitamin A was thermostable during simulated cooking conditions with concomitant longer shelf life when compared to the free vitamin A. In addition, cooked and light-irradiated encapsulated vitamin A was highly bioaccessible compared to the free-treated vitamin [175]. The above studies demonstrate 14 Journal of Food Processing and Preservation that encapsulation does not only protect BASs from environmental factors but also enhances their bioavailability and bioaccessibility maximizing absorption and thus exerting health benefits to human.…”
Section: Biosafety and Bioavailabilitymentioning
confidence: 81%
See 1 more Smart Citation
“…The results showed that encapsulated vitamin A was thermostable during simulated cooking conditions with concomitant longer shelf life when compared to the free vitamin A. In addition, cooked and light-irradiated encapsulated vitamin A was highly bioaccessible compared to the free-treated vitamin [175]. The above studies demonstrate 14 Journal of Food Processing and Preservation that encapsulation does not only protect BASs from environmental factors but also enhances their bioavailability and bioaccessibility maximizing absorption and thus exerting health benefits to human.…”
Section: Biosafety and Bioavailabilitymentioning
confidence: 81%
“…In vivo experiments further demonstrated the significant bioavailability of fucoxanthin in blood plasma compared to the control PE [174]. Others have recently encapsulated vitamin A in FDA-approved basic methacrylate copolymer to curb the menace of vitamin A deficiency [175]. The results showed that encapsulated vitamin A was thermostable during simulated cooking conditions with concomitant longer shelf life when compared to the free vitamin A.…”
Section: Biosafety and Bioavailabilitymentioning
confidence: 97%